Swim turn performances at the Sydney 2000 Olympic Games - Mason, B.; Cossor, J. (coachesinfo.com)
Swim turn performances of the top 16 finalists at the Sydney Olympics were analysed to identify the better characteristics of elite performance. Overhead cameras were used to obtain timing, distance and velocity characteristics of the push off and underwater phases of turns. This information supplemented the race analysis data that provided the time for the in phase and out phase of turns. The most significant aspect of the turn was the underwater phase. Swimmers that had a further distance and longer time underwater, during the out phase of the turn, in butterfly, backstroke and breaststroke events gained a greater advantage from quicker turns than swimmers with lesser underwater distances.